The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1432-2277.2009.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative pretransplant serostatus forToxoplasma gondiiis associated with impaired survival after heart transplantation

Abstract: Summary Chronic Toxoplasma gondii infection is known to trigger potentially adverse immunoregulatory changes, but limited data exist on long‐term implications for heart transplant (HTX) recipients. We evaluated the risk of all cause mortality regarding T. gondii serostatus prior to HTX. Pre‐HTX T. gondii serostatus was obtained in 344 recipients and 294 donors. Mean age was 52.1 ± 10.2 years and mean follow‐up time after HTX was 5.7 (±5.5, median 3.5) years. All seronegative patients received prophylaxis with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 6 publications
2
5
2
9
Order By: Relevance
“…With a median of 5.5 years of follow-up, the authors noted that Toxoplasma seropositivity was associated with increased mortality even after adjustment for potential confounders including age, hypertension, smoking status, and serum creatinine. This is in stark contrast to the results of a study by Doesch et al in 2010, in which 344 heart transplant recipients transplanted between 1989 and 2008 at the University of Heidelberg in Germany were examined (4). With a median of 5.7 years of follow-up, the authors noted that Toxoplasma seronegativity was associated with increased mortality even after adjustment for potential confounders including age, serum creatinine, cytomegalovirus serostatus, diabetes, ischemic time, azathioprine versus mycophenolate mofetil immunosuppression, and number of treated rejection episodes.…”
contrasting
confidence: 74%
“…With a median of 5.5 years of follow-up, the authors noted that Toxoplasma seropositivity was associated with increased mortality even after adjustment for potential confounders including age, hypertension, smoking status, and serum creatinine. This is in stark contrast to the results of a study by Doesch et al in 2010, in which 344 heart transplant recipients transplanted between 1989 and 2008 at the University of Heidelberg in Germany were examined (4). With a median of 5.7 years of follow-up, the authors noted that Toxoplasma seronegativity was associated with increased mortality even after adjustment for potential confounders including age, serum creatinine, cytomegalovirus serostatus, diabetes, ischemic time, azathioprine versus mycophenolate mofetil immunosuppression, and number of treated rejection episodes.…”
contrasting
confidence: 74%
“…Searching for an explanation of the contradictory results of the studies of Arora et al ( 1 ) and Doesch et al ( 2 ) and our study, we demonstrated several differences between the studies. A summary is presented in Table 5.…”
Section: Discussioncontrasting
confidence: 52%
“…However, oral folinic acid administration prevents the negative side effects of a pyrimethamine-sulfadiazine regimen in most cases. This study, as well as the studies by Arora et al ( 1 ) and Doesch et al ( 2 ), did not identify a difference in mortality between Toxoplasma seronegative recipients that received the heart of a seropositive versus a seronegative donor, suggesting that the antibiotic prophylactic drugs given to Toxoplasma mismatch recipients (D+/R-) do not negatively affect outcome.…”
Section: Discussionsupporting
confidence: 51%
“…19 This result supports the idea of importance of prophylactic anti-toxoplasma treatment among these cases.Thus, clinicians should be well-informed about the risk of T gondii infection in patients receiving heart transplant. In another study by Doesch et al,20 from 344 heart transplant adults, 55.2% were seronegative and 44.8% were seropositive before transplantation. In the long-term follow-up, 152 of them died.…”
mentioning
confidence: 90%